\[\boxed{\mathbf{756\ (756).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[Запишем:\ \]
\[\ \frac{1}{a + c} = \frac{\frac{1}{b + c} + \frac{1}{a + b}}{2}\text{\ \ }\]
\[\frac{2}{a + c} = \frac{1}{b + c} + \frac{1}{a + b}\]
\[\frac{2}{a + c} = \frac{a + b + b + c}{(b + c)(a + b)}\text{\ \ }\]
\[\frac{2}{a + c} = \frac{a + c + 2b}{(b + c)(a + b)}\text{\ \ }\]
\[\frac{2}{a + c} = \frac{a + c + 2b}{ab + b^{2} + ac + bc}\ \]
\[2 \cdot \left( ab + b^{2} + ac + bc \right) =\]
\[= (a + c)(a + c + 2b)\]
\[2ab + 2b^{2} + 2ac + 2bc =\]
\[= a^{2} + ac + 2ab + ac +\]
\[+ c^{2} + 2bc\]
\[2b^{2} = a^{2} + c^{2}\ или\ \ \ \ \]
\[b^{2} = \frac{a^{2} + c^{2}}{2}\text{\ \ }\]
\[Тогда:\ \ \]
\[a^{2},\ b^{2},\ c^{2} - тоже\ члены\]
\[\ арифметической\ прогрессии.\]
\[\boxed{\mathbf{756.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ 6ab² - 12ab^{3} =\]
\[= 6ab\left( b - 2b^{2} \right) = 6ab²(1 - 2b)\]
\[2)\ 2a³ - 8a = 2a\left( a^{2} - 4 \right) =\]
\[= 2a(a - 2)(a + 2)\]
\[3)\ 3a²c - 3c^{3} = 3c\left( a^{2} - c^{2} \right) =\]
\[= 3c(a - c)(a + c)\]
\[4)\ 18mn² + 27m²n =\]
\[= 9mn(2n + 3m)\]
\[5)\ 100x² - 1 =\]
\[= (10x - 1)(10x + 1)\]
\[6)\ 2y² - 12y + 18 =\]
\[= 2 \cdot \left( y^{2} - 6y + 9 \right) = 2 \cdot (y - 3)²\]